2019
DOI: 10.1186/s12917-019-1934-5
|View full text |Cite
|
Sign up to set email alerts
|

Acorn-related acquired pseudomelanosis in Calabrian black pigs

Abstract: Background Melanosis of lymph nodes in black pigs has generally been related to regression of congenital melanoma and, occasionally, to ingestion of acorns. The aim of this manuscript is to confirm the hypothesis of a possible acquired acorn-related pseudomelanosis in the Nero Calabrese pig , a swine breed belonging to the group of Italian native breeds and whose coverage area corresponds to the region of Calabria, southern Italy. This pig is characterized by slow-growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Experimental studies demonstrated that macroscopic lesions may be found in cattle 14 days post-infection [ 45 ], but in some instances, 6–8 weeks are required [ 46 ], and, especially in early infection, lesions are invisible to the naked eye. However, despite its low sensitivity and apparently low contribution in bTB surveillance system, post-mortem inspection at the slaughterhouse allows the detection of residual infection cases [ 21 , 24 , 25 , 47 ], also providing essential epidemiological data on zoonotic diseases [ 48 , 49 ] and allowing the documentation of several pathological findings [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies demonstrated that macroscopic lesions may be found in cattle 14 days post-infection [ 45 ], but in some instances, 6–8 weeks are required [ 46 ], and, especially in early infection, lesions are invisible to the naked eye. However, despite its low sensitivity and apparently low contribution in bTB surveillance system, post-mortem inspection at the slaughterhouse allows the detection of residual infection cases [ 21 , 24 , 25 , 47 ], also providing essential epidemiological data on zoonotic diseases [ 48 , 49 ] and allowing the documentation of several pathological findings [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%